Application of the Student Teams Achievement Division (STAD) Type Learning Model to Increase Student Activity and Learning Outcomes in the Basics of Plant Cultivation Subject in Class X ATP SMKN 6 Takalar - Puspita, Nofia Suci; Lahming, Lahming; Rahman, Khaidir (Formosa Journal of Applied Sciences, 2024)
Improving learning outcomes and student engagement in class X is the aim of this research at ATP SMKN 6 Takalar. Use of the independent variable for the research is that the Student Team Achievement Division (STAD) oversees research projects and educational objectives using student engagement variables. Students in the class were used as research samples. Learning activities are recorded through the use of student activity observation sheets. and Utilizing tests before and after measuring learning outcomes. Based on data analysis, it was determined that the activities and learning objectives of Takalar students in class X ATP SMKN 6 could be improved using a learning model known as Student Teams Achievement Division, or STAD.